Re-examining Arabic Grammar Pedagogy for Non-Native Learners in Islamic Higher Education: A Case Study at Sekolah Tinggi Ilmu Tarbiyah Syamsuddhuha, North Aceh - Makmur Akbar; Muhammad Ediyani; Ferry Rusda (Educenter : Jurnal Ilmiah Pendidikan, 2026)
Arabic grammar instruction in Islamic higher education has traditionally emphasized rule-based learning to support students’ understanding of classical Islamic texts. However, limited research has explored how grammar teaching is implemented for non-native Arabic learners and how lecturers balance traditional approaches with communicative language teaching. This study investigates Arabic grammar pedagogy at Sekolah Tinggi Ilmu Tarbiyah Syamsuddhuha through a qualitative case study involving six lecturers and twenty undergraduate students. Data were collected through interviews, classroom observations, and document analysis, then analyzed thematically. The findings indicate that grammar instruction remains largely teacher-centered and deductive, focusing on rule explanation, memorization, and textual analysis. While this approach strengthens students’ explicit grammatical knowledge and supports engagement with classical Arabic texts, it often limits classroom interaction and communicative language use. Many students reported difficulties applying grammatical knowledge in authentic speaking and writing contexts. In contrast, classes incorporating inductive and interactive activities showed greater student participation and contextual understanding. The study concludes that Arabic grammar teaching should adopt a more balanced model that combines traditional grammatical rigor with communicative and learner-centered approaches to enhance language acquisition among non-native learners.